Determination of arsenic content of available traditional medicines in Malaysia using hydride generation atomic absorption spectrometry - Helal Uddin, A.B.M.; Khalid, Reem S.; Khan, Umeed Ali; Abbas, Syed Atif (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2013)
Purpose: To determine the content of arsenic (As) in some locally available traditional medicines in the East Coast region of Malaysia. Methods: The determination of As was conducted using hydride generation-atomic absorption spectrometry (HG-AAS). Sample preparation entailed mineral acid digestion using hydrochloric acid and nitric acid mixture in a ratio of 1:3. Sixty samples were collected from different locations including shops and open markets in East Coast region of Malaysia, namely, Pahang, Terengganu and Kelantan states. Most of these preparations were not registered with Malaysian drug authority. Results: Out of sixty traditional medicine samples, twenty six contained As in a concentration range of 0.2150 - 1.3254 ppm. As for the rest, they were below the limit of quantification (LOQ). Conclusion: Traditional medicine samples available in the east coast region of Malaysia contain levels of arsenic that can adversely affect health upon consumption.